Evaluation of the possibilities of implementation of the American OPI test system and the determination of its effectiveness for the Kazakh language pronunciation subtest - Kuzembekova Ж.Ж.; Demesinova Ж.О. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article examines the American OPI test system and its application to the speaking subtest in Kazakh language testing, considering future development. It argues that updating Kazakh language assessments with a focus on speaking can expand the language’s functional scope. The findings provide theoretical foundations for test developers in designing speaking tasks. The study employs methods of compilation, comparison, and analysis. As linguists and native speakers, we aim to promote the state language’s broader use and transition into everyday communication. This requires thorough research and the adoption of best global practices. Integrating the OPI test system into Kazakh language assessment, particularly its speaking component, is a necessary step. Since the speaking subtest enhances communicative skills and highlights key linguistic features, attention must be given to its format, content, and structure. Incorporating an internationally recognized system will further elevate the status of the Kazakh language.